Extremely low-frequency magnetic field exposure level for Koreans by occupational code - Joon Sig Jung; Mailan Arachchige Don Rajitha Kawshalya; In Keun Shim; Jung Min Ryu; Myung Hee Kwon; Duck Shin Park; Seung Cheol Hong (Emerging Contaminants, 2018)
This study attempted to identify the level of exposure of 350 subjects to the extremely low-frequency magnetic field (ELF-MF). The occupational group showed significantly high levels of ELF-MF in every exposure indicator during work and transportation (p < 0.05). About 11% and 6% of the members of the occupational group were exposed to over 2 mG and 4 mG, respectively, of ELF-MF during ''all'' activities. The 24-h ELF-MF exposure levels of the subjects in both groups were analyzed. In the occupational group, for every activity, the percentile for less than 2 mG corresponded to 100% of C-4 (agriculture), 95% of C-1 (professional), 97% of C-2 (engineer, office/sales), 81% of C-3 (services), 85% of C-5 (technician, labor management), and 50% of C-6 (electrician). In the non-occupational group, the percentile for less than 2 mG corresponded to 92% of students, 83% of homemakers, 81% of the elderly, and 88% of the unemployed. The percentile for over 4 mG was 5% for students, homemakers, and the elderly and 13% of the unemployed. Electricians and the unemployed had the highest ELF-MF levels in both groups, respectively. Electricians were exposed to ELF-MF mostly at work, while the unemployed subjects were most affected by the activities classified under sleep and transportation. Keywords: ELF-MF, EMF, Exposure assessment, Occupational code, Occupational exposure